2015
DOI: 10.4306/pi.2015.12.1.118
|View full text |Cite
|
Sign up to set email alerts
|

CRY1 Variations Impacts on the Depressive Relapse Rate in a Sample of Bipolar Patients

Abstract: ObjectiveA relevant part of the social and personal burden caused by Bipolar Disorder (BD) is related to depressive phases. Authors investigated the genetic impact of a set of variations located in CRY1, a gene involved in the control of the circadian rhythms, towards depressive episodes in a sample of bipolar patients from the STEP-BD sample. As a secondary analysis, CYR1 variations were analyzed as predictors of sleep disruption.Methods654 bipolar patients were included in the analysis. Data were available g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…This may not always be easy, with regard to some overlap of symptoms, but there are, at least, several types of depression that can be related to circadian dysfunction. Evidence for this conclusion is, in part, based on the associations with mutations in genes of core and accessory elements of cellular circadian oscillators, such as Per2, Cry2, Bmal1 (= Arntl) and Npas2 in winter depression (Johansson et al, 2003;Lavebratt et al, 2010aLavebratt et al, , 2010bPartonen et al, 2007;Rajendran and Janakarajan, 2016), as well as Per3, Cry2, Bmal1 (Arntl), Bmal2 (Arntl2), Clock, Dbp, Tim, CsnK1ε and NR1D1 (Rev-erbα; Ear1) in bipolar disorder (Benedetti et al, 2008;Dallaspezia et al, 2016;Dallaspezia andBenedetti, 2015, 2011;Drago et al, 2015;Gonzalez et al, 2015;Kripke et al, 2009;Le-Niculescu et al, 2009;Mansour et al, 2006;Nievergelt et al, 2006;Partonen, 2014;Sjöholm et al, 2010). While the role of the circadian system was discovered relatively early in seasonal affective and bipolar disorders, involvement in MDD appeared to be rather uncertain for quite some time.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…This may not always be easy, with regard to some overlap of symptoms, but there are, at least, several types of depression that can be related to circadian dysfunction. Evidence for this conclusion is, in part, based on the associations with mutations in genes of core and accessory elements of cellular circadian oscillators, such as Per2, Cry2, Bmal1 (= Arntl) and Npas2 in winter depression (Johansson et al, 2003;Lavebratt et al, 2010aLavebratt et al, , 2010bPartonen et al, 2007;Rajendran and Janakarajan, 2016), as well as Per3, Cry2, Bmal1 (Arntl), Bmal2 (Arntl2), Clock, Dbp, Tim, CsnK1ε and NR1D1 (Rev-erbα; Ear1) in bipolar disorder (Benedetti et al, 2008;Dallaspezia et al, 2016;Dallaspezia andBenedetti, 2015, 2011;Drago et al, 2015;Gonzalez et al, 2015;Kripke et al, 2009;Le-Niculescu et al, 2009;Mansour et al, 2006;Nievergelt et al, 2006;Partonen, 2014;Sjöholm et al, 2010). While the role of the circadian system was discovered relatively early in seasonal affective and bipolar disorders, involvement in MDD appeared to be rather uncertain for quite some time.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…In this study, the expression levels of Per1, Per2, and Per3 were downregulated in CUMS rats compared with those of healthy control rats, suggesting that low expression of Per1/2/3 accounted for the depression-like behavior in CUMS rats. Second, Cry1 is a gene involved in the control of the circadian rhythms, and it impacts the depressive relapse rate in a sample of bipolar patients . Studies have shown that altered circadian clock function and high expression of the Cry1 were found in the nucleus accumbens (NAc) of depression mice .…”
Section: Resultsmentioning
confidence: 99%
“…Second, Cry1 is a gene involved in the control of the circadian rhythms, and it impacts the depressive relapse rate in a sample of bipolar patients. 45 Studies have shown that altered circadian clock function and high expression of the Cry1 were found in the nucleus accumbens (NAc) of depression mice. 46 In this study, the expression of Cry1 was upregulated in CUMS rats; it may cause depression-like behavior in CUMS rats.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphism of CRY1 and CACNA1C may also change the response to clopidogrel, though this does not appear to occur through influence on mRNA expression. One study suggested that rs10861688 in CRY1 is associated with depressive events, 34 and another study showed that CACNA1C rs2007044 affects activation of the left IFG, leading to schizophrenia susceptibility 35 . Therefore, circadian rhythm genes in general influence the clopidogrel antiplatelet effect through related emotional changes, but the underlying mechanism needs further investigation at molecular to cellular levels.…”
Section: Discussionmentioning
confidence: 99%